2021
DOI: 10.1007/s12250-020-00343-x
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangement of Actin Cytoskeleton by Zika Virus Infection Facilitates Blood–Testis Barrier Hyperpermeability

Abstract: In recent years, various serious diseases caused by Zika virus (ZIKV) have made it impossible to be ignored. Confirmed existence of ZIKV in semen and sexually transmission of ZIKV suggested that it can break the blood–testis barrier (BTB), or Sertoli cell barrier (SCB). However, little is known about the underlying mechanism. In this study, interaction between actin, an important component of the SCB, and ZIKV envelope (E) protein domain III (EDIII) was inferred from co-immunoprecipitation (Co-IP) liquid chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 58 publications
0
12
0
1
Order By: Relevance
“…Although these viruses cannot directly cross the BTB, the inflammatory factors they secrete can cause the TJ proteins between supporting cells to degrade, disrupting the structure and function of the BTB and allowing viruses to invade the spermatogenic tubules. The interaction of ZIKV E with F-actin causes the F-actin network to reorganize, jeopardizing BTB integrity ( Nie et al, 2021 ). When Sertoli cells are exposed to inflammatory mediators originating from ZIKV-infected macrophages, the ZO-1 protein is degraded, which is associated with enhanced BTB permeability ( Siemann et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these viruses cannot directly cross the BTB, the inflammatory factors they secrete can cause the TJ proteins between supporting cells to degrade, disrupting the structure and function of the BTB and allowing viruses to invade the spermatogenic tubules. The interaction of ZIKV E with F-actin causes the F-actin network to reorganize, jeopardizing BTB integrity ( Nie et al, 2021 ). When Sertoli cells are exposed to inflammatory mediators originating from ZIKV-infected macrophages, the ZO-1 protein is degraded, which is associated with enhanced BTB permeability ( Siemann et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…To analyze the citations of the documents, cocitation analysis of the cited references was performed (Figure 5B; Table 5). There were a total of 40,575 cited references; the most highly cited references were Cheng C. Yan (Cheng and Mruk, 2012), Mruk DD (Mruk and Cheng, 2004), Vogl AW (Vogl et al, 2008), Meng J (Meng et al, 2005), Cheng C. Yan (Cheng and Mruk, 2002), Cheng C. Yan (Cheng and Mruk, 2010), Yan HHN (Yan et al, 2008), Mazk DD (Yan et al, 2008), O'donnell Liza (O'Donnell et al, 2011), and Pelletier RM (Pelletier, 2011).…”
Section: Citationsmentioning
confidence: 99%
“…Sertoli cells have reported the roles of a particular protein [70] or its impact on the BTB [71]. However, this is the first study that uses mass spectrometry to understand global proteomic alterations induced by ZIKV infection in HSerC at 3, 5 and 7 dpi.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…To accomplish viral replication, assembly, and maturation, intracellular complexes of the virus utilize intracellular cytoskeletal components of the host to move from the periphery of the cell to sites of RNA synthesis [ 30 ]. Microtubules and actin are important components of the cellular cytoskeleton that facilitates flavivirus intracellular translocation to the nucleus [ 31 33 ]. In our study, we observed that DTMUV-infected DEF included a number of upregulated DEG that regulate the action cytoskeleton signaling pathway, such as FGF (fibroblast growth factor) family members (FGF1/3/4/5/19) and scaffold protein IQGAP2, which play a role in stabilizing microtubules [ 34 36 ] (Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%